1996
DOI: 10.1038/sc.1996.75
|View full text |Cite
|
Sign up to set email alerts
|

The origin and significance of spinal cord pulsation

Abstract: We studied the origin and mechanism of spinal cord pulsation in ten dogs in order to elucidate its clinical significance. Under general anesthesia, a 6 cm length of the animals' cervical spinal cord was exposed and the cerebrospinal fluid removed. The amplitude of spinal pulsation was then measured by means of ultrasonography in Mode M. The measurements were made after the spinal cord was cut: (I) on the cranial side; (2) on the cranial as well as caudal side, with the nerve roots and radicular arteries intact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 2 publications
2
36
0
Order By: Relevance
“…2 There are two concepts regarding the origin of the lumbar cerebrospinal¯uid pulse wave (L-CSFPW): that it arises from pulsation of the spinal cord. 3,4 and that it is due to pulsation of the brain which is transmitted through the subarachnoid space of the spine. 5,6 We recently demonstrated in dogs that L-CSFPW re¯ects pulsation of both the spinal cord and brain by analyzing the e ect on it of the occulusion of tha aorta and vena cava using system analysis; this showed the possibility that L-CSFPW could be an indicator of the spinal cord blood¯ow.…”
Section: Introductionmentioning
confidence: 99%
“…2 There are two concepts regarding the origin of the lumbar cerebrospinal¯uid pulse wave (L-CSFPW): that it arises from pulsation of the spinal cord. 3,4 and that it is due to pulsation of the brain which is transmitted through the subarachnoid space of the spine. 5,6 We recently demonstrated in dogs that L-CSFPW re¯ects pulsation of both the spinal cord and brain by analyzing the e ect on it of the occulusion of tha aorta and vena cava using system analysis; this showed the possibility that L-CSFPW could be an indicator of the spinal cord blood¯ow.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that some motion of the spinal cord may arise from blood flow in the radicular arteries, 35 but the bulk of the motion is expected to be caused by CSF flow. 36,37 The magnitude of displacement depends on the rostral-caudal position with the cord and on its curvature, as can be observed in serial images of the spinal cord with sagittal slices.…”
Section: Problems Arising From Motionmentioning
confidence: 99%
“…One additional refinement that has been introduced recently is the ability to replicate the very small, heartbeatdriven 'breathing mode' pulsations of the spinal cord [12], which are ≈100 µm in amplitude. This is done by embedding an angioplasty balloon axially within the silicone parenchyma of the mock spinal cord at moulding.…”
Section: Discussionmentioning
confidence: 99%